B cell rich meningeal inflammation associates with increased spinal cord pathology in multiple sclerosis. (26th April 2020) - Reali, Camilla; Magliozzi, Roberta; Roncaroli, Federico; Nicholas, Richard; Howell, Owain W.; Reynolds, Richard
Abstract: Increased inflammation in the cerebral meninges is associated with extensive subpial cortical grey matter pathology in the forebrain and a more severe disease course in a substantial proportion of secondary progressive multiple sclerosis (SPMS) cases. It is not known whether this relationship extends to spinal cord pathology. We assessed the contribution of meningeal and parenchymal immune infiltrates to spinal cord pathology in SPMS cases characterized in the presence (F+) or absence (F−) of lymphoid‐like structures in the forebrain meninges. Transverse cryosections of cervical, thoracic and lumbar cord of 22 SPMS and five control cases were analyzed for CD20+ B cells, CD4+ and CD8+ T cells, microglia/macrophages (IBA‐1+), demyelination (myelin oligodendrocyte glycoprotein+) and axon density (neurofilament‐H+). Lymphoid‐like structures containing follicular dendritic cell networks and dividing B cells were seen in the spinal meninges of 3 out of 11 F+ SPMS cases. CD4+ and CD20+ cell counts were increased in F+ SPMS compared to F− SPMS and controls, whilst axon loss was greatest in motor and sensory tracts of the F+ SPMS cases ( P < 0.01). The density of CD20+ B cells of the spinal leptomeninges correlated with CD4+ T cells and total B and T cells of the meninges; with the density of white matter perivascular CD20+ and CD4+ lymphocytes ( P < 0.05); with white matter lesion area ( P < 0.05); and the extent of axon loss ( P < 0.05) in F+ SPMS cases only. We show that the presence of lymphoid‐like structures in the forebrain is associated with a profound spinal cord pathology and local B cell rich meningeal inflammation associates with the extent of cord pathology. Our work supports a principal role for B cells in sustaining inflammation and tissue injury throughout the CNS in the progressive disease stage.